Malaysian IVF patients must be warned about US lawsuits involving PGT-A (PGS) - Heng, Alexis Boon Chin; Roslan, Rosazra; Muhsin, Sayyed Mohamed (Social Health Analytics Sdn Bhd, 2024)
In Malaysia, IVF patients are frequently encouraged to add costly preimplantation genetic testing for aneuploidy (PGT-A) to their IVF treatment, intended to screen for chromosomal abnormalities. However, evidence on PGT-A’s effectiveness in increasing live birth rates is limited, particularly in certain age groups. Despite this, many IVF patients are unaware that PGT-A has received a "red light" rating in the UK due to concerns over its impact on IVF success rates. Critics argue that some companies have misled patients to profit from their vulnerability, violating core healthcare principles like "non-maleficence."